2012
DOI: 10.1371/journal.pone.0029959
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 Treatment Delays Cellular Aging in Human Mesenchymal Stem Cells while Maintaining Their Multipotent Capacity

Abstract: 1,25-dihydroxyvitamin D3 (1,25D3) was reported to induce premature organismal aging in fibroblast growth factor-23 (Fgf23) and klotho deficient mice, which is of main interest as 1,25D3 supplementation of its precursor cholecalciferol is used in basic osteoporosis treatment. We wanted to know if 1,25D3 is able to modulate aging processes on a cellular level in human mesenchymal stem cells (hMSC). Effects of 100 nM 1,25D3 on hMSC were analyzed by cell proliferation and apoptosis assay, β-galactosidase staining,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…After activation, MSCs mediate immunosuppression through the secretion of soluble mediators (such as nitric oxide, prostaglandin E2, indoleamine 2,3-dioxygenase, and IL-6) and up-regulation of modulatory molecules (including galectins, PDL1, TGF-β, and HLA-G) (Meisel et al, 2004;Maby-El Hajjami et al, 2009;Ghannam et al, 2010). Recent evidence has demonstrated that calcitriol inhibits MSC-proliferationinduced cell cycle arrest and promotes accumulation of MSCs in the G0/G1 phase without inducing apoptosis (Artaza et al, 2010;Klotz et al, 2012). These effects were associated with a decrease in the GTPase Rho and the atypical Rho family GTPase Rhou/Wrch-1 expression without inducing Wnt-1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After activation, MSCs mediate immunosuppression through the secretion of soluble mediators (such as nitric oxide, prostaglandin E2, indoleamine 2,3-dioxygenase, and IL-6) and up-regulation of modulatory molecules (including galectins, PDL1, TGF-β, and HLA-G) (Meisel et al, 2004;Maby-El Hajjami et al, 2009;Ghannam et al, 2010). Recent evidence has demonstrated that calcitriol inhibits MSC-proliferationinduced cell cycle arrest and promotes accumulation of MSCs in the G0/G1 phase without inducing apoptosis (Artaza et al, 2010;Klotz et al, 2012). These effects were associated with a decrease in the GTPase Rho and the atypical Rho family GTPase Rhou/Wrch-1 expression without inducing Wnt-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent documents have shown that calcitriol has an important role in regulating the growth of MSCs (Artaza et al, 2010;Klotz et al, 2012). The present study was carried out to investigate the effects of calcitriol on the interaction between bone-marrow-derived MSCs and neutrophils in rats.…”
Section: Introductionmentioning
confidence: 97%
“…The precise mechanism of how the ligand/VDR complex may help protect individuals against cardiovascular diseases is not clear. It has been documented that vitamin D has functional roles in cellular proliferation, including different stages of the cell cycle, differentiation, and apoptosis [17, 18] that could have impact on normal angiogenesis and endothelial cell differentiation [19]. VDR is expressed in almost all tissues and in a wide variety of cell types, including cardiomyocytes, vascular smooth muscle cells, and endothelial cells [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…One technique for accomplishing this is the treatment of cells in vitro with 1,25-dihydroxyvitamin D3 [39]. Klotz et al showed that treatment of human mesenchymal stem cells with 1,25-dihydroxyvitamin D3 (1,25D3) delays signs of senescence while simultaneously helping the stem cells retain their multipotent capacities (Fig.…”
Section: Strategy #2: Preventing Senescencementioning
confidence: 99%
“…Additionally, the treated cells showed down-regulated expression of the aging-related gene p16 INK4a , and significantly less cell death after 72 h when compared to the control groups. However, the 1,25D3 treatment simply delayed senescence while allowing the cells to retain their multi-potent qualities; it did not influence the cells to differentiate into any specific lineage, so if this treatment is to be used, it must be used in conjunction with a differentiating agent [39]. To retain multi-potency, it is essential to conserve a population of quiescent cells so that in case of future injury, these cells can readily contribute to the healing process.…”
Section: Strategy #2: Preventing Senescencementioning
confidence: 99%